164k views
3 votes
HELP!!!! Simplify -2i x (-2i)

HELP!!!! Simplify -2i x (-2i)-example-1

2 Answers

3 votes

Answer:

- 4

Explanation:

note that i² = (
√(-1))² = - 1

- 2i × - 2i

= - 2 × - 2 × i² = 4 × - 1 = - 4


User Roland Bouman
by
4.8k points
5 votes

Answer:

-4

Explanation:

-2i times (-2i) can be rewritten as (-2)^2*i^2.

Recalling that i^2 = -1, we then have (-2)^2*(-1)

Completing this evaluation, we get -4.

User David Alsh
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.